Faktor-Faktor yang Mempengaruhi Nyeri Punggung Ibu Hamil Trimester III: Literatur Review - Melati Nur Arummega; Alfiah Rahmawati; Arum Meiranny (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2022)
Back pain is caused by pain in the lumbosacral area. The increase in intensity with increasing gestational age results from a shift in the center of gravity and changes in body posture. Back pain from sacroiliac/lumbar can be a long term back pain if not treated promptly. Literature review aims to examine more deeply about back pain in pregnant women in the third trimester, there were factors that influence it by reviewing. Methods literature review by searching on Google Scholar and PubMed. The keyword criteria are